Electrode, electrode manufacturing method, ion sensor, device and method for measuring components in a living body

By introducing internal solid-state layers of metal oxides and solid electrolytes into the ion sensor electrodes, the problem of potential instability of traditional electrodes is solved, and higher potential stability and longer service life are achieved.

JP7628508B2Active Publication Date: 2025-02-10SYSMEX CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021569834
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-10
Filing Date
2020-12-24
Publication Date
2025-02-10
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

The potential of traditional ion sensor electrodes is unstable during multiple use or long-term use, resulting in frequent calibration and increased frequency of electrode replacement, affecting measurement accuracy and reliability.

Method used

An electrode design is adopted for an internal solid-state layer containing metal oxides and solid electrolytes, and the potential stability of the electrode is improved by forming an internal solid-state layer on the electrode material.

Benefits of technology

It provides higher potential stability, reduces frequent calibration and replacement frequency of electrodes, and improves the service life and measurement accuracy of the ion sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628508000012
    Figure 0007628508000012
  • Figure 0007628508000013
    Figure 0007628508000013
  • Figure 0007628508000014
    Figure 0007628508000014
Patent Text Reader

Abstract

Provided is an electrode that exhibits higher potential-stability when used repeatedly and / or over a long period of time in an ion sensor. The electrode comprises: an electrode material; and an internal solid-state layer containing a metal oxide and a solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode, a method for manufacturing an electrode, an ion sensor, an apparatus for measuring a component in a living body, and a method for measuring a component in a living body. [Background technology]

[0002] An all-solid-state ion-selective electrode and an ion sensor using the same are known. For example, Non-Patent Document 1 describes an insertion material (Na 0.33 MnO2, Li a FePO4, K b A solid-state ion-selective electrode using MnO2·mH2O as the inner solid layer has been disclosed. 0.33 MnO2, Li a FePO4 or K b This electrode is formed by laminating an inner solid layer made of a mixture of MnO2·mH2O, a conductive agent (acetylene black), and a binder (PVDF), and then laminating an ion-selective membrane made of a base material (polyvinyl chloride) mixed with an ionophore, plasticizer, and an anion-rejecting agent on top of that. [Prior art documents] [Non-patent literature]

[0003] [Non-Patent Document 1] Shinichi Komaba, et al., “All-solid-state ion-selective electrodes with redox-active lithium, sodium, and potassium insertion materials as the inner solid-contact layer” Analyst, 142(20), 3857-3866 (2017). Summary of the Invention [Problem to be solved by the invention]

[0004] In the course of their research to obtain higher quality electrodes, the inventors have found that the potential of conventional electrodes in ion sensors becomes unstable and changes with repeated use and / or long-term use. This potential instability leads to increased frequency of calibration and electrode replacement. For this reason, conventional ion sensors are calibrated after each measurement or after multiple measurements at set time intervals. Therefore, an object of the present invention is to provide an electrode in an ion sensor that has higher potential stability against repeated use and / or long-term use. [Means for solving the problem]

[0005] The present inventors have conducted intensive research in view of the above problems, and have found that the above problems can be solved by an electrode including an internal solid layer containing a metal oxide and a solid electrolyte, and an electrode material. Based on this finding, the present inventors have conducted further research, and have completed the present invention.

[0006] That is, the present invention includes the following aspects.

[0007] Item A. An electrode comprising an inner solid layer containing a metal oxide and a solid electrolyte, and an electrode material. Item B. A method for producing an electrode, comprising forming an inner solid layer containing a metal oxide and a solid electrolyte on an electrode material. Item C. An ion sensor comprising an insulating substrate and the electrode according to item A arranged on the insulating substrate. Item D. A biological component measuring device including the ion sensor according to Item C, which measures the sodium ion concentration in tissue fluid collected from a subject. Item E. A method for measuring components in a living body, comprising measuring the sodium ion concentration in tissue fluid collected from a subject using the ion sensor described in Item C. Effect of the Invention

[0008] According to the present invention, it is possible to provide an electrode having higher potential stability against repeated use and / or long-term use in an ion sensor. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an electrode of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing an example of an ion selective electrode of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing an example of a reference electrode of the present invention. [Figure 4] FIG. 1 is a schematic cross-sectional view showing an example of an ion sensor of the present invention. [Diagram 5] FIG. 2 is a schematic cross-sectional view showing an example of a part of an ion sensor of the present invention. [Figure 6] FIG. 1 is a schematic cross-sectional view showing an example of an ion sensor of the present invention. [Figure 7] FIG. 1 is a schematic cross-sectional view showing an example of an ion sensor of the present invention. [Figure 8] FIG. 1 is a schematic plan view showing an example of an ion sensor of the present invention. [Figure 9] FIG. 2(a) is a perspective view of the device for measuring the components in a living body when the first cover is in a closed state, and (b) is a perspective view when it is in an open state. [Figure 10] FIG. 2(a) is an explanatory diagram showing a schematic configuration of the inside of the device for measuring the components in a living body as seen from a side, and FIG. 2(b) is an explanatory diagram showing the same as seen from the front. [Figure 11] FIG. [Figure 12] FIG. 2(a) is a perspective view of a glucose sensor and a sodium ion sensor, and FIG. 2(b) is a side view. [Figure 13] The arrangement of each material in a cross-sectional SEM image of the internal solid layer is shown. [Figure 14] The arrangement of each material in a cross-sectional SEM image of the internal solid layer is shown. [Figure 15] 1 shows the potential measurement results of Test Example 1. The horizontal axis indicates the Na concentration of the electrolyte solution, and the vertical axis indicates the measured potential. [Figure 16]1 shows the potential measurement results of Test Example 2. The horizontal axis shows the number of times the measurement was repeated, and the vertical axis shows the potential change (absolute value) from the first potential measurement. [Figure 17] The potential measurement results of Test Example 3 are shown. The horizontal axis indicates the mass ratio of the solid electrolyte. The vertical axis indicates the standard deviation of the potentials of three sets, in which a 2 mM Na solution was measured six times, a 30 mM solution was measured once, and a 2 mM solution was measured once, with three sets being performed consecutively. In each set, the potential of the 2 mM solution was measured the sixth time when the potential became stable. [Figure 18] The potential measurement results of Test Example 4 are shown. On the horizontal axis, "1" indicates the result on the first day, and "3" indicates the result on the third day. The vertical axis indicates the difference (absolute value) in the measured potential of the electrolyte solution of the same concentration obtained at the beginning and end of each day. [Figure 19] FIG. 13 is a schematic diagram showing an overview of a potential measuring method in Test Example 5. [Figure 20] 1 shows the results of potential measurement in Test Example 5. The horizontal axis shows the Na concentration of the electrolyte solution, and the vertical axis shows the potential difference from the measured potential at a Na concentration of 0.3 mM. [Figure 21] 1 shows the measured potential of Example 5 relative to a commercially available Ag / AgCl (internal solution: saturated KCl) electrode having an internal solution in Test Example 5. [Figure 22] 1 shows the results of potential measurement in Test Example 6. The vertical axis shows the difference in potential measured immediately after immersion in the electrolyte solution for 1.5 hours and the potential measured after 1.5 hours. [Figure 23] 1 shows the potential measurement results of Test Example 7. The vertical axis shows the standard deviation of the potential of a 30 mM solution. [Figure 24] 1 shows the results of potential measurement in Test Example 8. The horizontal axis shows the K concentration of the electrolyte solution, and the vertical axis shows the measured potential. [Diagram 25] 1 shows the potential measurement results of Test Example 8'. The vertical axis shows the potential fluctuation rate of the 1, 10, and 100 mM K solutions measured initially and the 1, 10, and 100 mM K solutions measured finally after 4.8 to 5 hours. [Figure 26] 1 shows the potential measurement results of Test Example 9. The vertical axis shows the potential fluctuation rate of the 1, 10, and 100 mM K solutions measured initially and the 1, 10, and 100 mM K solutions measured finally after 4.8 to 5 hours. [Figure 27] 1 shows the potential measurement results of Test Example 10. The vertical axis shows the standard deviation of the potential of a K10 mM solution. [Figure 28] This shows the results of potential measurement in Test Example 11. The vertical axis shows the absolute value of the difference between the potential measured one minute after immersion in a 10 mM solution, a 100 mM solution, and a 1 mM solution in that order after stabilizing each electrode in a 1 mM K solution, and the potential measured last in the 1 mM K solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this specification, the expressions "contain" and "comprise" include the concepts of "contain", "include", "consist essentially of" and "consist only of".

[0011] 1. Electrode In one aspect, the present invention relates to an electrode (sometimes referred to as the "electrode of the present invention" in this specification) including an internal solid layer containing a metal oxide and a solid electrolyte, and an electrode material. This will be described below.

[0012] The metal oxide is not particularly limited as long as it can be used as an electrode of an ion sensor. When the electrode of the present invention is used as an ion-selective electrode in an ion sensor, the metal oxide can preferably be one that can perform insertion and removal of a measurement ion in a crystal structure with the transfer of electrons (ion-electron conductor).

[0013] The measurement ion is not particularly limited, but examples thereof include sodium ion, potassium ion, calcium ion, magnesium ion, etc., preferably sodium ion, potassium ion, etc., and particularly preferably sodium ion.

[0014] The metal oxide can be appropriately selected depending on the ion to be measured. Specific examples of the metal oxide include M x MnO2, M x NiO2, M x CoO2, Mx Ni 0.5 Mn 0.5 O2, M x FeO2, M 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, M x Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2, M x Ni 0.5 Ti 0.5 O2, M x VO2, M x CrO2, M x FePO4 (wherein M is independently Na or K, and x represents any positive number). Examples thereof include etc. Among these, more preferably M x MnO2 is included, and particularly preferably Na x MnO2 is included.

[0015] x is usually 0 < x ≤ 1. x is preferably 0.15 to 0.66, more preferably 0.2 to 0.5, still more preferably 0.22 to 0.28, 0.30 to 0.36, or 0.41 to 0.47, and particularly preferably 0.245 to 0.255, 0.325 to 0.335, or 0.435 to 0.445.

[0016] The crystal structure of the metal oxide is not particularly limited as long as it can be used as an electrode of the ion sensor. Examples of the crystal structure include, for example, a cubic crystal structure, a tetragonal crystal structure, a trigonal crystal structure, a hexagonal crystal structure, a rhombohedral crystal structure, a triclinic crystal structure, a monoclinic crystal structure, etc. Among these, a cubic crystal structure is preferably included.

[0017] The form of the metal oxide is not particularly limited, but is preferably particulate. The particles of the metal oxide can be of any shape, such as flake-like, rod-like, columnar, spherical, ellipsoidal, etc., and are preferably flake-like.

[0018] The average particle size of the metal oxide particles is preferably 1 to 20 μm, more preferably 2 to 15 μm, and even more preferably 5 to 12 μm, from the viewpoint of increasing the adhesion between the metal oxide and the solid electrolyte and improving the performance as an electrode of an ion sensor. The average particle size can be measured by a laser diffraction / scattering type particle size distribution measuring device.

[0019] The metal oxide may be one type alone or two or more types in combination.

[0020] The content of the metal oxide is, for example, 20 to 70 mass %, preferably 25 to 65 mass %, and more preferably 30 to 60 mass %, relative to 100 mass % of the inner solid layer.

[0021] The solid electrolyte is not particularly limited as long as it is a solid capable of conducting ions. When the electrode of the present invention is used as an ion-selective electrode in an ion sensor, the solid electrolyte can be one capable of conducting the ions to be measured. Typically, the solid electrolyte can be an ion (measurement ion) conductive ceramic.

[0022] The measurement ion is not particularly limited, but examples thereof include sodium ion, potassium ion, calcium ion, magnesium ion, etc., preferably sodium ion, potassium ion, etc., and particularly preferably sodium ion.

[0023] The solid electrolyte can be appropriately selected depending on the ion to be measured. Specific examples of the solid electrolyte include oxide-based solid electrolytes such as β" alumina, β alumina, perovskite-type oxides, NASICON-type oxides, and garnet-type oxides, sulfide-based solid electrolytes, stabilized zirconia, α-silver iodide, and zeolite (zeolite can contain cations such as Na ions, K ions, and H ions inside). Among these, β" alumina, β alumina, and zeolite are particularly preferred from the viewpoint of high stability against water and suitable use as an electrode for an ion sensor.

[0024] β" / β alumina has a layered structure consisting of an ion conductive layer and a spinel block, and the movement of ions (measurement ions) occurs within the ion conductive layer. β" alumina and β alumina differ in their crystal structures, and of these, β" alumina has a higher sodium ion content within its crystal structure and has relatively high ionic conductivity. β" / β alumina is preferably Na-β" / β alumina that can conduct sodium ions. Na-β" alumina is usually a substance having a chemical composition of Na2O·xAl2O3 (x=5-7). Na-β alumina is usually a substance having a chemical composition of Na2O·xAl2O3 (x=9-11).

[0025] The form of the solid electrolyte is not particularly limited, but is preferably particulate. The solid electrolyte particles may have any shape, such as scale, rod, column, sphere, or ellipsoid.

[0026] In one embodiment of the present invention, the average particle size of the solid electrolyte particles is preferably 0.02 to 3 μm, more preferably 0.1 to 1 μm, and even more preferably 0.15 to 0.5 μm, from the viewpoint of increasing the adhesion between the metal oxide and the solid electrolyte and improving the performance as an electrode of an ion sensor. In another embodiment of the present invention, from the same viewpoint, the average particle size of the solid electrolyte particles is preferably 0.02 to 7, more preferably 0.05 to 5, and even more preferably 0.1 to 3 μm. The average particle size can be measured by a laser diffraction / scattering type particle size distribution measuring device.

[0027] In the internal solid layer, the average particle size of the solid electrolyte is preferably smaller than the average particle size of the metal oxide. Specifically, in one aspect of the present invention, the average particle size of the solid electrolyte is, for example, 0.1 to 30, preferably 0.5 to 10, more preferably 1 to 5, relative to the average particle size of the metal oxide being 100. In another aspect of the present invention, the average particle size of the solid electrolyte is, for example, 0.1 to 70, preferably 0.5 to 60, more preferably 1 to 5, relative to the average particle size of the metal oxide being 100.

[0028] The solid electrolyte may be one type alone or two or more types in combination.

[0029] The content of the solid electrolyte is, for example, 15 to 70 mass %, preferably 20 to 65 mass %, and more preferably 25 to 60 mass %, relative to 100 mass % of the inner solid layer.

[0030] The mass ratio of the metal oxide to the solid electrolyte in the internal solid layer (metal oxide:solid electrolyte) is, for example, 5:1 to 1:5, preferably 2:1 to 1:2, more preferably 1.5:1 to 1:1.5, even more preferably 1.2:1 to 1:1.2, and still more preferably 1.1:1 to 1:1.1.

[0031] The internal solid layer preferably contains a conductive agent, which can improve the electrical conductivity of the internal solid layer, improve the buffering effect against volume changes caused by the inflow and outflow of ions, and enhance the electrode stability.

[0032] The conductive agent is not particularly limited, but examples thereof include carbon materials such as carbon black, acetylene black, ketjen black, carbon nanotubes, graphene, carbon powder, and graphite powder, conductive fibers such as metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, organic conductive materials such as phenylene derivatives and graphene derivatives, etc. Among these, carbon materials are preferable.

[0033] The conductive agent may be a single type, or a combination of two or more types.

[0034] The content of the conductive agent is, for example, 0.1 to 20 mass %, preferably 1 to 15 mass %, and more preferably 2 to 10 mass %, relative to 100 mass % of the inner solid layer.

[0035] The mass ratio of the metal oxide (or solid electrolyte) to the conductive agent in the internal solid layer (metal oxide (or solid electrolyte):conductive agent) is, for example, 20:1 to 1:1, preferably 15:1 to 3:1, and more preferably 10:1 to 6:1.

[0036] The internal solid layer preferably contains a binder, which allows the components in the internal solid layer to be more firmly bound together.

[0037] The binder is not particularly limited, but for example, polyvinylidene fluoride, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, acrylic emulsion, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, polymers such as carboxymethylcellulose, similar compounds having the same skeleton as these polymers, and composite agents consisting of multiple polymers can be used. Among these, preferred are polyvinylidene fluoride, a mixture containing styrene butadiene latex and carboxymethylcellulose (SBR / CMC), a mixture containing polyamideimide and carbodiimide, polytetrafluoroethylene, acrylic emulsion, etc., and more preferred is polyvinylidene fluoride.

[0038] The binder may be one type alone or two or more types in combination.

[0039] The content of the binder is, for example, 0.1 to 20 mass %, preferably 1 to 15 mass %, and more preferably 2 to 10 mass %, relative to 100 mass % of the inner solid layer.

[0040] The mass ratio of the metal oxide (or solid electrolyte) to the binder in the inner solid layer (metal oxide (or solid electrolyte):binder) is, for example, 20:1 to 1:1, preferably 15:1 to 3:1, and more preferably 10:1 to 6:1.

[0041] The inner solid layer may contain other components in addition to those mentioned above, such as raw materials for producing solid electrolytes and metal oxides, such as MnCO3, Na2CO3, and Al2O3.

[0042] The total content of the metal oxide and solid electrolyte in the internal solid layer (and, when a conductive agent and a binder are further contained, the total content including them) is, for example, 70 to 100 mass%, preferably 80 to 100 mass%, more preferably 90 to 100 mass%, even more preferably 95 to 100 mass%, and still more preferably 99 to 100 mass%, relative to 100 mass% of the internal solid layer.

[0043] The layer structure of the internal solid layer is not particularly limited. The internal solid layer may have a single-layer structure consisting of one layer made of a single composition, or may have a multi-layer structure consisting of multiple layers made of the same or different compositions.

[0044] The thickness of the internal solid layer is not particularly limited as long as the electrical conductivity is not significantly impaired. The thickness is, for example, 1 to 200 μm. From the viewpoints of production efficiency, production cost, and the like, the thickness is preferably 1 to 100 μm, more preferably 1 to 50 μm, and further preferably 1 to 20 μm.

[0045] The electrode material is not particularly limited as long as it contains a conductive material. Examples of the conductive material include metals such as platinum, gold, silver, copper, carbon, palladium, chromium, aluminum, and nickel, alloys containing at least one of these metals, and metal halides such as chlorides of these metals. Among these, preferred are platinum, gold, silver, palladium, aluminum, nickel, and carbon. The conductive material may be one type alone or two or more types in combination.

[0046] The content of the conductive material is, for example, 70 to 100 mass %, preferably 85 to 100 mass %, and more preferably 95 to 100 mass %, relative to 100 mass % of the electrode material.

[0047] The shape of the electrode material is not particularly limited, but is usually flat.

[0048] The layer structure of the electrode material is not particularly limited. The electrode material may have a single-layer structure consisting of one layer made of a single composition, or a multi-layer structure consisting of multiple layers made of the same or different compositions.

[0049] The thickness of the electrode material is not particularly limited as long as the electrical conductivity is not significantly impaired. The thickness is, for example, 1 to 10 μm. From the viewpoints of production efficiency, production costs, etc., the thickness is preferably 1 to 5 μm.

[0050] In the electrode of the present invention, the internal solid layer is usually disposed directly on the electrode material or via another layer. Preferably, the internal solid layer is disposed directly on the electrode material. One embodiment of the electrode of the present invention is shown in FIG. 1. In the electrode, it is preferable to dispose the internal solid layer so as to cover the side surface of the electrode material, or to provide a side wall, so that the electrode material is not exposed.

[0051] The electrode of the present invention can be suitably used as an ion-selective electrode, a reference electrode, or the like.

[0052] When the electrode of the present invention is used as an ion-selective electrode, it is preferable that the electrode of the present invention further comprises an ion-selective membrane. The ion-selective membrane contains an ion-selective substance.

[0053] As the ion-selective substance, conventionally known ionophores or synthetic substances can be widely used. The ion-selective substance can be selected according to the ion to be measured. As the ion-selective substance, an ionophore is preferably used. Examples of the ionophore include valinomycin, monesin, rhodopsin, nonactin, monactin, ionomycin, gramicidin A, nigericin, CCCP (carbonyl cyanide-m-chlorophenylhydrazone), FCCP (carbonyl cyanide-p-trifluoromethoxyphenylhydrazone), and the like. Examples of the synthetic substance include crown ethers (a group of macrocyclic polyethers), and further non-cyclic nonylphenoxypolyethanol. The ion-selective substance may be one type alone or two or more types in combination. Specific examples of the ion-selective substance include DD16C5, Bis-12Crown-4, 12-Crown-4, 15-Crown-5, 18-Crown-6, and kalexarene.

[0054] The ion selective membrane usually contains a binder resin. The binder resin is not particularly limited. Specific examples of the binder resin include polyvinyl chloride, polyvinylidene chloride, polyacrylonitrile, polyurethane, polyvinyl acetate, silicone elastomer, polyvinyl alcohol, cellulose ester, polycarbonate, vinyl chloride / vinyl acetate copolymer, vinyl chloride / vinyl acetate / vinyl alcohol copolymer, vinyl chloride / vinylidene chloride copolymer, and the like. The binder resin may be one type alone or two or more types in combination.

[0055] The ion selective membrane preferably contains a plasticizer. The plasticizer increases the flexibility of the ion selective membrane, and thus, for example, the occurrence of cracks in the ion selective membrane can be suppressed. The plasticizer is not particularly limited, and examples thereof include TEHP (tris(2-ethylhexyl) phosphate), NPOE (2-nitrophenyl octyl ether), DOP (dioctyl phthalate), DOS (dioctyl sebacate), DBE (dibasic acid ester), BA (butyl acrylate), and the like. The plasticizer may be one type alone or two or more types in combination.

[0056] The ion selective membrane preferably contains an anion rejecting agent. The anion rejecting agent can be selected according to the ion to be measured. Examples of the anion rejecting agent include tetraphenylborate salts such as sodium tetrakis(4-chlorophenyl)borate (Na-TCPB), potassium tetrakis(4-chlorophenyl)borate (K-TCPB), sodium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (Na-TFPB), potassium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (K-TFPB), potassium tetraphenylborate (K-TPB), sodium tetraphenylborate (Na-TPB), and sodium tetrakis[3,5-bis(1,1,1,3,3,3-hexafluoro-2-methoxy-2-propyl)phenyl]borate. The anion rejecting agent may be one type alone or two or more types in combination.

[0057] The contents of the above components are not particularly limited as long as the ion selective membrane can function. The contents relative to 100% by mass of the ion selective membrane are, for example, 3 to 10% by mass for the ion selective substance, 15 to 45% by mass for the binder resin, 50 to 80% by mass for the plasticizer, and 1 to 5% by mass for the anion rejector.

[0058] The layer structure of the ion selective membrane is not particularly limited. The ion selective membrane may have a single layer structure consisting of one layer made of a single composition, or a multi-layer structure consisting of multiple layers made of the same or different compositions.

[0059] The thickness of the ion selective membrane is not particularly limited and is, for example, 50 to 300 μm.

[0060] The use of the ion selective membrane is not particularly limited, and it is, for example, a membrane selective for cations such as sodium ions and potassium ions.

[0061] The ion selective membrane is disposed on the internal solid layer. Preferably, the ion selective membrane is disposed directly on the internal solid layer. One embodiment of the ion selective electrode of the present invention is shown in FIG. 2. In the ion selective electrode, it is preferable to dispose the internal solid layer so as to cover the side surface of the electrode material as well, provide a side wall, etc., so that the electrode material is not exposed. In the ion selective electrode, it is preferable to dispose the ion selective membrane so as to cover the side surface of the internal solid layer as well, provide a side wall, etc., so that the internal solid layer is not exposed.

[0062] When the electrode of the present invention is used as a reference electrode, it is preferable that the electrode of the present invention further comprises a layer (sometimes referred to as a "salt bridge layer" in this specification) that functions as a salt bridge and can suppress the influence of changes in external ion concentration. An ionic liquid gel film can be suitably used as such a layer.

[0063] The ionic liquid is not particularly limited, but may be, for example, an ionic liquid in which the cation is at least one of an imidazolium cation, a pyridinium cation, a piperidinium cation, a pyrrolidinium cation, a quaternary ammonium cation, a phosphonium cation, or an arzonium cation, and the anion is [R 1 SO2NSO2R 2 ]-(R 1 , R 2 are perfluoroalkyl groups having 1 to 5 carbon atoms), borate ions containing fluorine and tetravalent boron, bis(2-ethylhexyl) sulfosuccinate, AlCl4 - , Al3Cl7 - , NO3 - , BF4 - , PF6 - , CH3COO- , CF3COO - , CF3SO3 - , (CF3SO2)2N - , (CF3SO2)3C - , AsF6 - , SbF6 - , F(HF)n - , CF3CF2CF2CF2SO3 - , (CF3CF2SO2)2N - , or CF3CF2CF2COO - The hydrophobic ionic liquid may be at least one of the above.

[0064] The method for gelling the hydrophobic ionic liquid is not particularly limited, but the liquid can be gelled using a polymer compound. Examples of such polymer compounds include vinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyethyl methacrylate, polyacrylonitrile, polybutyl acrylate, polyvinylpyridine, organic electrolyte oligomers (such as those in which the main chain cationic portion has a PICPM structure), polyvinyl chloride, and other synthetic rubbers. A crosslinking agent may be used together with the polymer, and for example, a gelling agent containing a crosslinking agent having a plurality of fluoroalkylated sulfonyl amide groups and a polymer compound having a group capable of forming an onium salt with the crosslinking agent may be used. A plasticizer may also be used together with the polymer, and for example, the plasticizer may be mixed with polyvinyl chloride and dried to gel it. As the plasticizer, the same plasticizer as that used in the ion selective membrane described above may be used.

[0065] The layer structure of the salt bridge layer is not particularly limited, and may be a single-layer structure consisting of one layer made of a single composition, or a multi-layer structure consisting of multiple layers made of the same or different compositions.

[0066] The salt bridge layer is disposed on the internal solid layer. Preferably, the salt bridge layer is disposed directly on the internal solid layer. One embodiment of the reference electrode of the present invention is shown in FIG. 3. In the reference electrode, it is preferable to dispose the internal solid layer so as to cover the side surface of the electrode material as well, or to provide a side wall on the side surface, so that the electrode material is not exposed. In the reference electrode, it is preferable to dispose the salt bridge layer so as to cover the side surface of the internal solid layer as well, or to provide a side wall on the side surface, so that the internal solid layer is not exposed.

[0067] The method for producing the electrode of the present invention is not particularly limited. Preferably, the electrode of the present invention can be produced by a method including forming an internal solid layer containing a metal oxide and a solid electrolyte on an electrode material.

[0068] The method for forming the internal solid layer is not particularly limited. Preferably, the internal solid layer can be formed by forming a film of a composition containing a metal oxide and a solid electrolyte on an electrode material and drying it. As the film forming method, electrostatic coating, coating with a dispenser, screen printing, sputtering, vapor deposition, etc. can be adopted, but electrostatic coating is preferred from the viewpoint of increasing the adhesion between the metal oxide and the solid electrolyte.

[0069] Other layers such as an ion selective membrane and a salt bridge layer can be formed by a method similar to that described above, that is, by forming a film of a composition (paste, solution, etc.) containing each component constituting the layer on the internal solid layer and drying it.

[0070] 2. Ion sensor In one aspect, the present invention relates to an ion sensor (sometimes referred to as the "ion sensor of the present invention" in this specification) including an insulating substrate and an electrode of the present invention disposed on the insulating substrate. This will be described below.

[0071] The insulating substrate is not particularly limited as long as it contains an insulating material that does not affect the conductivity of the electrodes. Examples of the insulating material include polyester resins such as polyvinyl alcohol, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polybutylene naphthalate; polyimide; glass epoxy resin; glass; ceramics; and fiber substrates such as paper.

[0072] In one embodiment of the present invention, the ion sensor of the present invention comprises an electrode of the present invention which is an ion-selective electrode, a schematic cross-sectional view of which is shown in FIG.

[0073] The reference electrode may be a reference electrode having an internal liquid, an all-solid-state reference electrode, or the like. Specifically, the reference electrode may be, for example, an Ag / AgCl electrode designed to maintain a constant Cl concentration on its surface (e.g., provided with a resin film that retains Cl ions), or the electrode of the present invention including a salt bridge layer. A schematic cross-sectional view of a portion of the ion sensor of the present invention in the latter case is shown in FIG. 5.

[0074] In one embodiment of the present invention, the ion sensor of the present invention includes the electrode of the present invention, which is an ion-selective electrode, and a reference electrode, as shown in FIG.

[0075] In one embodiment of the present invention, the ion sensor of the present invention includes an electrode of the present invention that is an ion-selective electrode and an electrode of the present invention that is a reference electrode. A schematic cross-sectional view of this case is shown in FIG.

[0076] The ion sensor of the present invention may optionally include other portions such as electrode leads, etc. An example of a preferred embodiment of the ion sensor of the present invention is shown in FIG.

[0077] The ion sensor of the present invention can be preferably used as a sodium ion sensor.

[0078] By contacting the object to be measured (e.g., tissue fluid collected from a subject, a substance that retains tissue fluid, etc.) with the electrodes in the ion sensor of the present invention and measuring the potential between the ion selective electrode and the reference electrode, the ion concentration in the object to be measured can be calculated based on the obtained measurement value.

[0079] 3.Bio-component measuring device In one aspect, the present invention relates to an apparatus for measuring components in a living body (sometimes referred to as "the apparatus for measuring components in a living body of the present invention" in this specification) that includes the ion sensor of the present invention and that measures a sodium ion concentration contained in interstitial fluid collected from a subject. This will be described below.

[0080] The device for measuring components in a living body of the present invention is not particularly limited as long as it includes the ion sensor of the present invention and can measure the concentration of ions such as sodium ions in a measurement object. The device for measuring components in a living body of the present invention preferably includes the ion sensor of the present invention, a detection unit, a control means, an operation display unit, and a power source (preferably further includes a glucose ion sensor, a reagent storage unit, and a liquid delivery unit). Hereinafter, a preferred embodiment of the device for measuring components in a living body of the present invention will be described with reference to Figs. 9 to 12.

[0081] The device for measuring components in a body 1 includes a mounting section 20 on which a tissue collection body 110 that has collected interstitial fluid is mounted, a glucose sensor 21 that acquires a signal reflecting the amount of a component to be measured contained in the interstitial fluid while in contact with the interstitial fluid collection body 110 mounted on the mounting section 20, and a moving section 60 that brings the interstitial fluid collection body 110 mounted on the mounting section 20 into contact with the glucose sensor 21 by changing the relative positions of the mounting section 20 and the glucose sensor 21 to a predetermined positional relationship. The device for measuring components in a body 1 acquires a signal reflecting the amount of glucose contained in the interstitial fluid by the glucose sensor 21, and measures the glucose concentration in the interstitial fluid. In addition, in this embodiment, the biological component measuring device 1 further includes a sodium ion sensor 22 that acquires a signal reflecting the amount of electrolytes contained in the tissue fluid when in contact with the interstitial fluid collection body 110 placed on the mounting section 20, and the moving section 60 changes the relative position between the mounting section 20 and the sodium ion sensor 22 to a predetermined positional relationship to bring the interstitial fluid collection body 110 placed on the mounting section 20 into contact with the sodium ion sensor 22, thereby acquiring a signal reflecting the amount of sodium ions contained in the tissue fluid and measuring the sodium ion concentration in the tissue fluid.

[0082] As shown in Figures 9 and 10, the biological component measuring device 1 at least comprises a detection section 2, a reagent storage section 3, a liquid delivery section 4, a control means 5, an operation display section 6, and a power supply 7, which are provided within a housing 10.

[0083] A first cover 11 is provided at the upper front of the housing 10 at a position adjacent to the operation display unit 6. The first cover 11 is a push-open type cover, and when pressed, the first cover 11 stands up and changes from the closed state shown in FIG. 9(a) to the open state shown in FIG. 9(b), exposing the installation unit 20 for installing the interstitial fluid collection body 110. A second cover 12 is provided on the upper surface of the housing 10. The second cover 12 is also a push-open type cover, and although not shown, when pressed, the second cover 12 stands up and changes from the closed state to the open state, exposing the glucose sensor 21 and the sodium ion sensor 22 of the detection unit 2, which will be described later. A third cover 13 is provided at the lower front of the housing 10. When the third cover 13 is opened, various tanks of the reagent storage unit 3 are exposed.

[0084] The detection unit 2 acquires signals related to the amount of components (glucose and electrolytes) contained in the interstitial fluid collected in the interstitial fluid collection body 110 and signals related to the amount of components (electrolytes) contained in the sweat collected in the sweat collection body 111. As shown in FIG. 11 , the detection unit 2 includes an installation unit 20, a glucose sensor 21, a sodium ion sensor 22, and a drive unit 23.

[0085] The installation section 20 is configured to install the interstitial fluid collection body 110 and the sweat collection body 111. The installation section 20 is composed of a sample plate 200 on which a support sheet 114 supporting the interstitial fluid collection body 110 and the sweat collection body 111 is placed, and a sample stage 201 on which the sample plate 200 is placed.

[0086] The sample plate 200 has a rectangular shape in a plan view, and has an outline that is slightly larger than the support sheet 114. The upper surface of the sample plate 200 is flat, and the support sheet 114 can be stably placed on the sample plate 200. This allows the sensors 21, 22 to be in good contact with the interstitial fluid collection body 110 and the sweat collection body 111 when measuring the interstitial fluid collection body 110 and the sweat collection body 111.

[0087] Small projections 2001 are provided at two corners on one end side in the longitudinal direction of the sample plate 200. The two small projections 2001 function as positioning parts for positioning the interstitial fluid collection body 110, and are fitted into two through holes formed in the support sheet 114 when the support sheet 114 is placed on the sample plate 200. This allows the support sheet 114 to be placed on the sample plate 200 without being misaligned, so that the interstitial fluid collection body 110 and the like can be positioned at an appropriate position relative to the sample plate 200. Furthermore, standing walls 2002A and 2002B having a height equal to or slightly greater than the thickness of the support sheet 114 are provided at two corners on the other end side in the longitudinal direction of the upper surface of the sample plate 200. When the support sheet 114 is placed on the sample plate 200, one of the two standing walls 2002A and 2002B abuts against the notch 117 of the support sheet 114, and the other standing wall 2002B fits along the side edge of the support sheet 114 opposite the notch 117. This makes it possible to more effectively position the support sheet 114 at an appropriate position on the sample plate 200. By holding the support sheet 114 on the sample plate 200 without misalignment in this way, the sensors 21 and 22 can be brought into good contact with the interstitial fluid collection body 110 and the sweat collection body 111 when measuring the interstitial fluid collection body 110 and the sweat collection body 111.

[0088] Furthermore, at the other end side in the longitudinal direction of the sample plate 200, a horizontal bar 2003 is bridged between the two standing walls 2002A, 2002B, and an insertion hole 2004 is formed between the upper surface of the sample plate 200 and the horizontal bar 2003. When the support sheet 114 is placed on the sample plate 200, a portion of the support sheet 114 on the other end side in the longitudinal direction is inserted into the insertion hole 2004. This prevents the support sheet 114 from floating up on the sample plate 200 by the horizontal bar 2003, and allows the support sheet 114 to be stably placed on the sample plate 200. This allows the sensors 21, 22 to be in good contact with the interstitial fluid collection body 110 and the sweat collection body 111 when measuring the interstitial fluid collection body 110 and the sweat collection body 111.

[0089] The sample stage 201 has a rectangular shape in a plan view, and has an outline that is slightly larger than the sample plate 200. The sample plate 200 is placed on the upper surface of the sample stage 201. The sample stage 201 is reciprocated in the X direction along the horizontal plane by a horizontal movement driving unit 230 of the driving unit 23, which will be described later. As a result, the interstitial fluid collection body 110 and the sweat collection body 111 are transported to positions below the sensors 21, 22.

[0090] Next, the glucose sensor 21 is a component detection sensor that obtains a signal reflecting the amount of glucose, which is a measurement target component contained in the tissue fluid, and functions as an acquisition unit. The sodium ion sensor 22 is a component detection sensor that obtains a signal reflecting the amount of sodium ions, which are auxiliary components contained in the tissue fluid, and functions as a second acquisition unit.

[0091] As shown in FIG. 12, each sensor 21, 22 includes a main body portion 210, 220 made of, for example, plastic, a slide portion 211, 221 made of, for example, plastic and slidably attached to the main body portion 210, 220, a cartridge portion 216, 226 made of, for example, plastic and detachably attached to the slide portion 211, 221, and an electrode portion 212, 222 attached to the underside of the cartridge portion 216, 226.

[0092] The main body 210, 220 has an upper part and a lower part, and has a step between the upper part and the lower part. The lower surface of the upper part is provided with terminals 213, 223 connected to the control means 5. An opening is formed in the lower part of the main body 210, 220, and the slide part 211, 221 protrudes from the opening. The main body 210, 220 is provided with a pressure absorbing member 217, 227. The pressure absorbing member 217, 227 may be a spring member such as a coil spring. The pressure absorbing member 217, 227 constitutes a pressure adjusting unit 61 that adjusts the contact pressure when the sensors 21, 22 contact the interstitial fluid collection body 110 to a constant value, and is included in the moving unit 60. The slide part 211, 221 is connected to the pressure absorbing member 217, 227, and slides up and down relative to the main body 210, 220 by the expansion and contraction of the pressure absorbing member 217, 227. When the sensors 21, 22 come into contact with the interstitial fluid collection body 110 or the sweat collection body 111, the pressure absorbing members 217, 227 expand and contract, displacing the electrode sections 212, 222 up and down, thereby making it possible to adjust the contact pressure of the electrode sections 212, 222 in contact with the interstitial fluid collection body 110 or the sweat collection body 111 to a constant level. Therefore, even if the shapes of the interstitial fluid collection body 110 or the sweat collection body 111 vary, the electrode sections 212, 222 can be brought into contact with the interstitial fluid collection body 110 or the sweat collection body 111 with a predetermined contact pressure. Note that the pressure absorbing members 217, 227 connected to the slide sections 211, 221 in the main bodies 210, 220 may not be one, but may be multiple.

[0093] Openings are formed in the lower portions of the slide portions 211, 221, and cartridge portions 216, 226 can be attached to the lower portions of the slide portions 211, 221 through these openings. Engagement holes 215, 225 are formed on both side surfaces of the lower portions of the slide portions 211, 221.

[0094] The cartridge parts 216, 226 are expendable items that are disposed of after being used a predetermined number of times to measure the interstitial fluid collection body 110 and the like. The cartridge parts 216, 226 are provided with a pair of locking claws 214, 224 corresponding to the respective locking holes 215, 225 of the slide parts 211, 221. The respective locking claws 214, 224 are locked into the corresponding locking holes 215, 225, so that the cartridge parts 216, 226 are held on the slide parts 211, 221. At this time, it is preferable that the cartridge parts 216, 226 are held so as to be able to swing, for example, by being slightly loose, without being fixed in position relative to the slide parts 211, 221. The cartridge parts 216, 226 constitute an angle adjusting part 62 that adjusts the angle at which the respective sensors 21, 22 contact the interstitial fluid collection body 110, and are included in the moving part 60. As a result, when the sensors 21, 22 come into contact with the interstitial fluid collection body 110 or the sweat collection body 111, the cartridge sections 216, 226 swing relative to the slide sections 211, 221 so as to move along the surfaces of the interstitial fluid collection body 110 or the sweat collection body 111. This makes it possible to adjust the angle of the surfaces of the electrode sections 212, 222 that come into contact with the interstitial fluid collection body 110 or the sweat collection body 111, and allows the electrode sections 212, 222 to come into good contact with the interstitial fluid collection body 110 or the sweat collection body 111 even if the shapes of the interstitial fluid collection body 110 or the sweat collection body 111 vary.

[0095] The electrode units 212, 222 each include a pair of a working electrode and a counter electrode, and a reference electrode. The electrode unit 212 for measuring glucose of the glucose sensor 21 has, for example, a working electrode formed with a glucose oxidase enzyme membrane on a platinum electrode, and a counter electrode made of a platinum electrode. On the other hand, the electrode unit 222 for measuring sodium ions of the sodium ion sensor 22 has, for example, a working electrode made of an ion selective electrode equipped with a sodium ion selective membrane, and a counter electrode made of a reference electrode.

[0096] The glucose sensor 21 includes a glucose measurement circuit (not shown) as an electric circuit connected to the electrode unit 212, and applies a constant voltage to the tissue fluid collected in the interstitial fluid collection body 110 by the electrode unit 212 contacting the interstitial fluid collection body 110, and obtains the current at that time as a detection value. This current value depends on the glucose concentration in the interstitial fluid. On the other hand, the sodium ion sensor 22 includes a sodium ion measurement circuit (not shown) as an electric circuit connected to the electrode unit 222, and obtains the voltage of the tissue fluid collected in the interstitial fluid collection body 110 or the sweat collected in the sweat collection body 111 as a detection value by the electrode unit 222 contacting the interstitial fluid collection body 110 or the sweat collection body 111. This voltage value depends on the sodium ion concentration in the interstitial fluid or the sweat. The glucose sensor 21 and the sodium ion sensor 22 are connected to the control means 5, and output the obtained current value or voltage value to the control means 5 as a detection signal. The control means 5 measures the glucose concentration and the sodium ion concentration based on the current value or voltage value included in the detection signal and the calibration curve stored in the memory unit.

[0097] The glucose sensor 21 and the sodium ion sensor 22 are set in the detection unit 2 by being attached to a mounting fixture 24. This mounting fixture 24 is attached to a pair of left and right side plates 16 (shown in FIG. 11) provided on the base plate 14 of the detection unit 2 so as to be vertically movable. A plurality of protrusions 243 are provided in the vertical direction on both side surfaces of the frame portion 240, and each protrusion 243 slides vertically in an elongated guide hole 17 (shown in FIG. 11) formed in each side plate 16, causing the mounting fixture 24 to move straight up and down.

[0098] Next, in this embodiment, the drive unit 23 moves the installation unit 20 and the sensors 21, 22 in order to bring the interstitial fluid collection body 110 installed on the installation unit 20 into contact with the sensors 21, 22, and is included in the movement unit 60. The drive unit 23 includes a horizontal movement drive unit 230 that moves the installation unit 20 in the horizontal direction, and a vertical movement drive unit 231 that moves the glucose sensor 21 and the sodium ion sensor 22 in the vertical direction. The vertical movement drive units 231 are provided in the detection unit 2 corresponding to the glucose sensor 21 and the sodium ion sensor 22, respectively.

[0099] The installation unit 20 is transported by the horizontal movement drive unit 230 among the installation position, the first measurement position, the second measurement position, and the third measurement position. In addition, as a method of positioning the installation unit 20 at each measurement position, an object detection sensor such as a photosensor may be provided at each measurement position, and the object detection sensor at each measurement position may detect the installation unit 20, thereby detecting that the installation unit 20 has reached each measurement position.

[0100] Each of the sensors 21 and 22 is transported by a vertical movement drive unit 231 among a standby position, a measurement position, and a cleaning position.

[0101] As a method for positioning each of the sensors 21, 22 at each position, a position detection sensor attached by the frame of the mounting fixture 24 may be used. The position detection sensor is fixed to a sensor support plate attached to the frame via a fixing device, and moves up and down together with the mounting fixture 24. In this example, a detection plate 92 is fixed to one side plate 16 (shown in FIG. 11 ) of the detection unit 2 so as to face the position detection sensor 9. The position detection sensor detects the upper and lower ends of the detection plate 92, thereby detecting the uppermost position (standby position) and the lowermost position (cleaning position) of each of the sensors 21, 22 that are moved up and down by the vertical movement drive unit 231.

[0102] Next, the reagent storage section 3 is provided with a waste liquid tank, a first tank for storing a cleaning liquid, a second tank for storing a low concentration calibration liquid for glucose, a third tank for storing a high concentration calibration liquid for glucose, a fourth tank for storing a medium concentration calibration liquid for sodium ions, and a fifth tank for storing a high concentration calibration liquid for sodium ions. The cleaning liquid in the first tank is used to clean the glucose sensor 21 and the sodium ion sensor 22, and is also used to create a calibration curve for sodium ions as a low concentration calibration liquid for sodium ions. An example of the cleaning liquid is a PB-K solution. The calibration liquid for glucose in the second tank and the third tank is used to create a calibration curve for glucose. An example of the calibration liquid for glucose is a PB-K solution to which glucose has been added. The glucose concentration of the PB-K solution is, for example, 0.5 mg / dL at low concentration, and is, for example, a concentration determined within a range of 10 mg / dL to 40 mg / dL at high concentration. The calibration liquid for sodium ions in the fourth tank and the fifth tank is used to create a calibration curve for sodium ions. An example of the calibration solution for sodium ions is saline. The medium concentration of sodium ions in saline is determined within a range of, for example, 1 mM to 2 mM, and the high concentration is determined within a range of, for example, 20 mM to 50 mM. Other examples of the calibration solution for sodium include a Tris solution and a PB-K solution. The glucose concentration or sodium ion concentration of each liquid in each tank is stored in the memory unit of the control means 5.

[0103] Next, the liquid delivery section 4 supplies the liquids stored in the tanks to the glucose sensor 21 and the sodium ion sensor 22 disposed in the detection section 2, and collects the delivered liquids in a waste liquid tank.

[0104] Next, the control means 5 controls the drive unit 23 to bring the interstitial fluid collection body 110 installed in the installation unit 20 into contact with each of the sensors 21 and 22, and is included in the moving unit 60. The control means 5 includes a microcomputer having a processor (e.g., a CPU) and a memory (e.g., a ROM and a RAM), a circuit for processing various signals such as a user interface control board, an I / O board, and an analog board. The control means 5 controls the operation of each part such as the detection unit 2, the liquid delivery unit 4, and the operation display unit 6 by the CPU reading and executing a program stored in the ROM. The RAM is used as a program development area when the program stored in the ROM is executed. The control means 5 has functions such as a control unit that controls the drive unit 23 of the detection unit 2, an analysis unit that calculates blood glucose AUC based on a signal reflecting the amount of the measurement target component (glucose) received from each of the sensors 21 and 22 of the detection unit 2 and a signal reflecting the amount of electrolytes (sodium ions) as auxiliary components, and a memory unit.

[0105] Next, the operation display unit 6 is used to give instructions to start measurement and to display analysis results. The operation display unit 6 can be configured with a touch panel display. The operation display unit 6 may be separated into an operation unit and a display unit, in which case the operation unit can be configured with buttons, switches, a keyboard, and a mouse.

[0106] Next, the power supply 7 converts an AC power supply voltage input from a power plug (not shown) into a DC voltage and supplies it to the control means 5. The power supply 7 is also connected to each of the other components and supplies power to each of them. EXAMPLES

[0107] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples.

[0108] The average particle size shown in the following test examples is the value of the cumulative frequency of 50% measured by a laser diffraction / scattering type particle size distribution analyzer. The thickness of each layer was obtained by measuring the corresponding layer with a contact type step gauge after coating and drying.

[0109] Test Example 1. Potential response of ion-selective electrode to NaCl concentration <Test Example 1-1. Preparation of ion-selective electrode (Example 1)> An ion-selective electrode (Example 1) was prepared as follows. Platinum paste was laminated on a ceramic substrate to form an electrode material with a diameter of 5 mm. A metal oxide (Na 0.33 MnO2 (orthogonal crystal structure), average particle size 8.9 μm, scale-like), solid electrolyte (β” alumina: Na2Al 10.6 O 15.9 A paste containing 16-crown-5 derivative (DD16C5: 16-crown-5 derivative with two decalino subunits), 68 parts by mass of plasticizer (TEHP: tris(2-ethylhexyl) phosphate), 1 part by mass of anion rejecter (Na-TFPB: sodium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate), and 29 parts by mass of base material (PVC: polyvinyl chloride) was laminated four times on the inner solid layer to form a Na ion-selective membrane with a thickness of 170 to 190 μm, and an ion-selective electrode was obtained.

[0110] The cross section of the ion-selective electrode was observed with a scanning electron microscope (SEM). In addition, the arrangement of each material in the cross section was investigated by EDX mapping. The arrangement of each material in the cross-sectional SEM image of the internal solid layer is shown in Figures 13 and 14. It was found that the metal oxide particles were surrounded by solid electrolyte particles with a smaller particle size than the metal oxide.

[0111] The mass ratios of the solid electrolyte, metal oxide, conductive agent, and binder in the internal solid layer are shown in the table below.

[0112] [Table 1]

[0113] <Test Example 1-2. Preparation of reference electrode> A reference electrode made of silver-silver chloride paste was formed by screen printing. A polyvinyl alcohol (PVA) film was laminated on the silver-silver chloride paste. The PVA film was soaked in a solution with a chloride ion concentration of 282 mM to stabilize the potential before use in the measurement.

[0114] <Test Example 1-3. Potential Measurement> An ion sensor consisting of an ion-selective electrode (Example 1) and a reference electrode was connected to a potentiometer, and then immersed in the following electrolyte solution (a mixed solution of NaCl and KCl, Na concentration: 0.3 mM, 2 mM, or 50 mM, K concentration: 280 mM, Cl concentration: Na concentration (mM) + 280 mM) to measure the potential. After each potential measurement, the electrode was washed with a cleaning solution (phosphate potassium buffer, Na concentration: 0.3 mM, K concentration: 280 mM).

[0115] <Test Example 1 Results> The results are shown in Figure 15. It was found that the ion-selective electrode with a solid electrolyte and an inner solid layer containing a metal oxide responded to Na concentration.

[0116] Test Example 2. Potential Stability of Ion-Selective Electrodes 1 <Test Example 2-1. Preparation of an ion-selective electrode (Comparative Example 1)> An ion-selective electrode was obtained in the same manner as in Example 1 without using a solid electrolyte (Comparative Example 1). The mass ratio of the inner solid layer of the ion-selective electrode used in the potential measurements below is shown in the table below.

[0117] [Table 2]

[0118] <Test Example 2-2. Electric potential measurement> Using an ion-selective electrode (Example 1 and Comparative Example 1), the same procedure as in Test Example 1-3 was carried out, except that a 30 mM Na solution was used as the electrolyte solution instead of a 50 mM Na solution. The measurement was repeated multiple times, and the electrode was washed after each measurement in the same manner as in Test Example 1-3. From each measurement value, the potential change (absolute value) from the first measured potential was calculated.

[0119] <Test Example 2 Results> The results are shown in Figure 16. It was found that the potential stability against repeated use was improved by further adding a solid electrolyte to the metal oxide in the internal solid layer.

[0120] Test Example 3. Potential Stability of Ion-Selective Electrodes 2 <Test Example 3-1. Preparation of ion-selective electrodes (Examples 2 to 3 and Comparative Example 2)> Ion selective electrodes (Example 2: solid electrolyte mass ratio 4, Example 3: solid electrolyte mass ratio 12) were obtained in the same manner as in Example 1, except that the mass ratio of the solid electrolyte was changed. Furthermore, an ion selective electrode (Comparative Example 2) was obtained in the same manner as in Example 1, except that no metal oxide was used. The mass ratios of the internal solid layers of the ion selective electrodes used in the potential measurements below are shown in the table below.

[0121] [Table 3]

[0122] <Test Example 3-2. Potential Measurement> Using an ion selective electrode (Examples 1 to 3 and Comparative Examples 1 to 2), the test was conducted in accordance with Test Examples 1 to 3, except that a 2 mM Na solution and a 30 mM Na solution were used as the electrolyte solution. In this test, three sets were consecutively conducted, with one set being a set in which the 2 mM Na solution was measured six times, the 30 mM solution was measured once, and the 2 mM solution was measured once. In each set, the sixth potential of the 2 mM solution, at which the potential became stable, was measured, and the standard deviation of the three sets of potentials was calculated.

[0123] <Test Example 3 Results> The results are shown in Figure 17. It was found that the potential stability against repeated use was improved by adding a solid electrolyte to the metal oxide in the internal solid layer. Furthermore, it was found that the potential fluctuation was large when a solid electrolyte was added but a metal oxide was not. This shows that the combination of metal oxide and solid electrolyte is important for potential stability against repeated use.

[0124] Test Example 4. Potential Stability of Ion-Selective Electrodes 3 <Test Example 4-1. Preparation of ion-selective electrode (Example 4)> An ion-selective electrode (Example 4) was obtained in the same manner as in Example 1, except that β-alumina (Na2O-11Al2O3, average particle size 0.26 μm) was used as the solid electrolyte. The mass ratio of the internal solid layer of the ion-selective electrode used in the potential measurements below is shown in the following table.

[0125] [Table 4]

[0126] <Test Example 4-2. Potential Measurement> The test was carried out in accordance with Test Example 1-3 using an ion-selective electrode (Examples 1 and 4). In this test, measurements were repeated throughout the day for three days. Based on the measured values, the difference (absolute value) in the measured potential of the electrolyte solution of the same concentration obtained at the beginning and end of each day was calculated, and the average value was calculated.

[0127] <Test Example 4 Results> The results are shown in Figure 18. It was found that whether β" alumina or β alumina was used as the solid electrolyte, high potential stability was obtained with repeated use.

[0128] Test Example 5. Potential Stability of Reference Electrode 1 <Test Example 5-1. Preparation of Reference Electrode (Example 5)> An electrode (Example 5) was prepared as follows. Platinum paste was laminated on a ceramic substrate to form an electrode material with a diameter of 5 mm. A metal oxide (Na 0.33MnO2 (orthogonal crystal structure), average particle size 8.9 μm, scale-like), solid electrolyte (β” alumina: Na2Al 10.6 O 15.9 A paste containing PVDF-HFP (Kynar Flex 2751-00 (HFP 15 mol%) manufactured by ARKEMA) and acetone was mixed at 1:10 (wt) and stirred overnight, and ionic liquid PP13-TFSI (Tokyo Chemical Industry Co., Ltd., 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide) was added thereto so that the ratio of PVDF-HFP:PP13-TFSI was 2:8. The resulting solution was applied to the internal solid layer, laminated 10 times while drying at 50 ° C., and finally dried at 150 ° C. to form an ionic liquid gel film, and an electrode was obtained. The mass ratios in the inner solid layer are shown in the table below.

[0129] [Table 5]

[0130] <Test Example 5-2. Potential Measurement> The same procedure as in Test Example 1-3 was followed, except that an electrode (Example 5) or an electrode made of silver-silver chloride paste (Comparative Example 3) was used instead of the ion-selective electrode, solutions with Na concentrations of 0.3, 1, 2, 10, and 30 mM were used as the electrolyte solution, and a commercially available Ag / AgCl (internal solution: saturated KCl) electrode with an internal solution was used as the reference electrode. The outline of the measurement method is shown in FIG.

[0131] <Test Example 5 Results> The potential difference calculated from the measured potential of the electrolyte solution with a Na concentration of 0.3 mM is shown in FIG. 20. Comparative Example 3 is an Ag / AgCl electrode without an internal liquid, so it responds to the Cl concentration, but Example 5 does not respond to the Na and Cl concentrations. It was found that an electrode that does not respond to the Na and Cl concentrations can be obtained by forming an ionic liquid gel film on an internal solid layer containing a solid electrolyte and a metal oxide. The measured potential of Example 5 for a commercially available Ag / AgCl (internal liquid: saturated KCl) electrode with an internal liquid is shown in FIG. 21. Even when solutions with different Na and Cl concentrations are measured, the potential difference between the commercially available reference electrode with an internal liquid and Example 5 is almost 0, and it can be seen that the electrode has the same performance as the commercially available reference electrode with an internal liquid. Therefore, this electrode can be used as a reference electrode.

[0132] Test Example 6. Potential Stability of Reference Electrode 2 <Test Example 6-1. Preparation of Reference Electrode (Example 6 and Comparative Example 4)> An electrode (Example 6) was obtained in the same manner as in Example 5, except that β-alumina (Na2O-11Al2O3, average particle size 0.26 μm) was used as the solid electrolyte. Furthermore, an electrode (Comparative Example 4) was obtained in the same manner as in Example 5, except that no solid electrolyte was used. The mass ratio of the internal solid layer of the electrodes used in the potential measurements below is shown in the table below.

[0133] [Table 6]

[0134] <Test Example 6-2. Potential Measurement> The same procedures as in Test Example 1-3 were carried out except that an electrode (Examples 5-6 and Comparative Example 4) was used instead of the ion selective electrode, a solution with a Na concentration of 2 mM and a K concentration of 268 mM was used as the electrolyte solution, and a commercially available Ag / AgCl (internal solution: saturated KCl) electrode with an internal solution was used as the reference electrode. In this test, each electrode was immersed in the electrolyte solution for 1.5 hours, and the measured potential was measured immediately after immersion and after 1.5 hours, and the difference between the measured potentials was calculated.

[0135] <Test Example 6 Results> The results are shown in Figure 22. It was found that the potential stability over long-term use was improved by further adding a solid electrolyte to the metal oxide in the internal solid layer.

[0136] Test Example 7. Potential Stability of Na Ion-Selective Electrode 3 <Test Example 7-1. Preparation of Na ion selective electrodes (Example 7 and Example 7')> A Na ion selective electrode (Example 7) was obtained in the same manner as in Example 1, except that the anion rejector was changed to K-TCPB. A Na ion selective electrode (Example 7') was obtained in the same manner as in Example 1, except that the solid electrolyte was changed to zeolite (Zeolam A-4 100# Tosoh, average particle size after processing 3 μm). The mass ratio of the internal solid layer and the anion rejector in the Na ion selective membrane for the electrodes used in the potential measurements below are shown in the table below.

[0137] [Table 7]

[0138] <Test Example 7-2. Potential Measurement> Using an ion selective electrode (Example 1, Example 7, and Example 7'), the test was conducted in accordance with Test Example 1-3, except that a 30 mM Na solution was used as the electrolyte solution. In this test, 11 sets were continuously conducted, with one set being a set in which a 2 mM Na solution was measured twice, a 0.3 mM solution once, a 2 mM solution once, and a 30 mM solution. The standard deviation of the potential of the 30 mM solution measured in each set was calculated. The standard deviation of the potential for three sets was calculated, and the average for the three sensors was calculated (only for Example 7', for one sensor).

[0139] <Test Example 7 Results> The results are shown in Figure 23. It was shown that the potential was stable regardless of the ion species in the selective membrane or the type of solid electrolyte.

[0140] Test Example 8. K ion concentration response of K ion selective electrode 1 <Test Example 8-1. Preparation of Na ion selective electrode (Example 8)> A K ion-selective electrode (Example 8) was prepared as follows: Platinum paste was laminated on a ceramic substrate to form an electrode material with a diameter of 5 mm. A paste containing a metal oxide (Na0.33MnO2 (rectangular crystal structure), average particle size 7.3 μm, flaky), solid electrolyte (β” alumina: Na2Al10.6O15.9, average particle size 0.99 μm), conductive agent (AB: acetylene black), and binder (PVDF: polyvinylidene fluoride) was layered on the electrode material by electrostatic coating to form an internal solid layer with a thickness of 10 μm. A paste containing 7 parts by mass of ionophore (valinomycin), 65 parts by mass of plasticizer (TEHP: tris(2-ethylhexyl) phosphate), 1 part by mass of anion rejecter (K-TCPB: potassium tetrakis(4-chlorophenyl)borate), and 27 parts by mass of base material (PVC: polyvinyl chloride) was layered four times on the internal solid layer to form a K ion selective membrane with a thickness of 170 to 190 μm, and a K ion selective electrode was obtained.

[0141] <Test Example 8-2. Potential Measurement> The potential was measured against Ag / AgCl, and converted from the solution concentration to the potential against Ag / AgCl (saturated KCl). The potential was measured at K concentrations of 1, 2, 4, 6, 8, 10, and 100 mM in a constant NaCl solution of 140 mM.

[0142] <Test Example 8 Results> The results are shown in Figure 24. It was found that the K ion concentration can also be measured by using a K ion selective membrane.

[0143] Test Example 8'. Potential stability of K ion selective electrode 1 <Test Example 8'-1. Preparation of K ion selective electrodes (Examples 9 to 10 and Comparative Example 5)> A K ion selective electrode (Example 9: solid electrolyte mass ratio 2.8, Example 10: solid electrolyte mass ratio 1.2) was obtained in the same manner as in Example 8, except that the mass ratio of the solid electrolyte was changed. Furthermore, a K ion selective electrode (Comparative Example 5) was obtained in the same manner as in Example 8, except that no solid electrolyte was used. The mass ratio of the inner solid layer and the anion rejector in the K ion selective membrane of the ion selective electrodes used in the potential measurements below are shown in the following table.

[0144] [Table 8]

[0145] <Test Example 8'-2. Potential Measurement> After measuring solutions of K1, 10, and 100 mM at a constant NaCl concentration of 140 mM, solutions of K1, 2, 4, 6, 8, and 10 mM at a constant NaCl concentration of 140 mM were measured. This was counted as one set, and measurements were repeated for six sets. Finally, solutions of K1, 10, and 100 mM at a constant NaCl concentration of 140 mM were measured. The sensor was washed with a cleaning solution of Na140 mM for each measurement. The potential fluctuation rate of the K1, 10, and 100 mM solutions measured initially and the K1, 10, and 100 mM solutions measured 4.8 to 5 hours later is shown in Figure 25.

[0146] <Test Example 8' Results> The results are shown in Figure 25. The results showed that the greater the amount of β-alumina added, the higher the potential stability.

[0147] Test Example 9. Potential Stability of K Ion-Selective Electrode 2 <Test Example 9-1. Preparation of K ion selective electrodes (Examples 11 to 13)> A K ion-selective electrode (Example 11: mass ratio of solid electrolyte 8, Example 12: mass ratio of solid electrolyte 2.8, Example 13: mass ratio of solid electrolyte 1.2) was obtained in the same manner as in Example 8, except that the solid electrolyte was changed to zeolite (Zeolam A-4 100# Tosoh, average particle size after processing 3 μm). For the ion-selective electrodes used in the potential measurements below, the mass ratio of the inner solid layer and the anion rejector in the K ion-selective membrane are shown in the following table.

[0148] [Table 9]

[0149] <Test Example 9-2. Potential Measurement> The test was carried out in the same manner as in Test Example 8'-2.

[0150] <Test Example 9 Results> The results are shown in Figure 26. The results showed that the greater the amount of zeolite added, the greater the potential stability.

[0151] Test Example 10. Potential Stability of K Ion-Selective Electrode 3 <Test Example 10-1. Preparation of K ion selective electrode (Example 14 and Comparative Example 6)> A K ion selective electrode was obtained in the same manner as in Example 8, except that the anion rejector was changed to Na-TFPB (Example 14). A K ion selective electrode was obtained (Comparative Example 6) by using a non-solid electrolyte Na2CO3 instead of the solid electrolyte of Example 8. The mass ratio of the inner solid layer and the anion rejector in the K ion selective membrane of the ion selective electrodes used in the potential measurements below are shown in the following table.

[0152] [Table 10]

[0153] <Test Example 10-2. Potential Measurement> The test was carried out in accordance with Test Example 8' using a K ion selective electrode (Examples 8, 11, and 14, Comparative Examples 5 and 6). The standard deviation of the potential of a K 10 mM solution measured a total of eight times during one day was calculated, and the average of the potentials of three sensors was calculated (only one sensor in Example 11).

[0154] <Test Example 10 Results> The results are shown in Figure 27. Whereas the potential fluctuated with Na2CO3, a non-solid electrolyte, the potential fluctuation was small with β-alumina and zeolite, which are solid electrolytes, regardless of the ion species in the selective membrane.

[0155] Test Example 11. Potential Stability of Reference Electrode 3 <Test Example 11-1. Preparation of Reference Electrodes (Examples 15 and 16)> The ratio of PVC to plasticizer was 1:2, and the ionic liquid [TBMOEP + ][C1C1N -] was dissolved in a THF solution, 20 μL was dropped onto the internal solid layer, and dried by heating at 60 ° C. to prepare a PVC membrane of ionic liquid gel. In Example 15, the plasticizer was NPOE, and in Example 16, the plasticizer was TEHP. Note that TBMOEP stands for tributyl (2-methoxyethyl) phosphonium bis- (trifluoromethanesulfonyl) imide. For the ion-selective electrodes used in the following potential measurements, the mass ratio of the internal solid layer and the plasticizer in the ionic liquid gel PVC membrane are shown in the following table.

[0156] [Table 11]

[0157] <Test Example 11-2. Potential Measurement> The same test as in Test Example 1-3 was performed except that an electrode (Examples 15 and 16) was used instead of the ion-selective electrode, a solution with a K concentration of 1, 10, and 100 mM and a Na concentration of 140 mM was used as the electrolyte solution, and a Ag / AgCl (internal solution: saturated KCl) electrode with a commercially available internal solution was used as the reference electrode. In this test, each electrode was stabilized with a K1 mM solution, and then immersed in a 10 mM solution, a 100 mM solution, and a 1 mM solution in that order, and the absolute value of the difference between the measured potential 1 minute after immersion and the potential measured last in the K1 mM solution was calculated.

[0158] <Test Example 11 Results> The results are shown in Figure 28. When any plasticizer was used, the potential difference was 1 mV or less regardless of the KCl concentration, and the potential was stable. [Explanation of symbols]

[0159] A internal solid layer B Electrode material C1 Ion selective membrane C2 Shiobashi layer D. Ion-selective electrode of the present invention E. Reference electrode of the present invention F Insulating substrate G reference electrode 1. Apparatus for measuring components in a living body according to the present invention

Claims

1. An inner solid layer containing a metal oxide and a solid electrolyte and formed by electrostatic coating; An electrode material; , an electrode.

2. an inner solid layer containing a metal oxide and a solid electrolyte; An ion selective membrane; An electrode material; , an electrode.

3. 3. The electrode according to claim 1, wherein the solid electrolyte is an ion-conducting ceramic.

4. 4. The electrode according to claim 1, wherein the solid electrolyte is a sodium ion or potassium ion conductive ceramic.

5. 5. The electrode of claim 1, wherein the solid electrolyte is β″ alumina or β alumina.

6. The electrode according to any one of claims 1 to 5, wherein the metal oxide is an ion-electron conductor.

7. 7. The electrode according to claim 1, wherein the metal oxide is an ion-electron conductor for sodium or potassium ions.

8. The metal oxide is M x MnO 2 (M represents Na or K, and x represents any positive number).

9. 9. The electrode of claim 8, wherein x is between 0.2 and 0.

5.

10. The electrode according to any one of claims 1 to 9, wherein the solid electrolyte and the metal oxide are in particulate form.

11. 11. The electrode of claim 10, wherein the average particle size of the solid electrolyte is smaller than the average particle size of the metal oxide.

12. 12. The electrode according to claim 1, wherein a mass ratio of the metal oxide to the solid electrolyte (metal oxide:solid electrolyte) in the internal solid layer is 2:1 to 1:

2.

13. The electrode according to any one of claims 1 to 12, wherein the internal solid layer contains a binder and a conductive agent.

14. The binder is (a) polyvinylidene fluoride, (b) an admixture containing styrene butadiene latex and carboxymethyl cellulose; (c) a mixture containing a polyamide, a polyimide, and a carbodiimide; (d) Polytetrafluoroethylene; and (e) Acrylic emulsion The electrode according to claim 13, which is at least one selected from the group consisting of:

15. 15. The electrode according to claim 13, wherein the conductive agent is at least one selected from the group consisting of carbon black, acetylene black, ketjen black, carbon nanotubes, graphene, carbon powder, and graphite powder.

16. 16. The electrode of claim 1, wherein the inner solid layer is disposed directly on the electrode material.

17. The electrode of claim 1 further comprising an ion selective membrane.

18. 20. The electrode of claim 2 or 17, wherein the ion selective membrane contains an ionophore.

19. 20. The electrode of claim 2, 17 or 18, wherein the ion selective membrane is disposed directly on the inner solid layer.

20. 20. The electrode of any one of claims 1 to 19, further comprising an ionic liquid gel membrane.

21. 21. The electrode of claim 20, wherein the ionic liquid gel film is disposed directly on the inner solid layer.

22. The electrode according to any one of claims 1 to 21, wherein the electrode material contains at least one selected from the group consisting of platinum, gold, silver, palladium, aluminum, nickel, and carbon.

23. A method for manufacturing an electrode, comprising forming an internal solid layer containing a metal oxide and a solid electrolyte on an electrode material, the method for forming the internal solid layer being electrostatic coating.

24. 1. A method for manufacturing an electrode, comprising: forming an internal solid layer containing a metal oxide and a solid electrolyte on an electrode material; and forming an ion selective membrane on the internal solid layer.

25. 24. The method of claim 23, comprising forming an ion selective membrane or an ionic liquid gel membrane on the inner solid layer.

26. A method for detecting a temperature rise in a liquid crystal display comprising: an insulating substrate; and an ion-selective electrode and a reference electrode disposed on the insulating substrate, An ion sensor, wherein the ion selective electrode is the electrode according to any one of claims 2 and 17 to 19.

27. A method for detecting a temperature rise in a liquid crystal display comprising: an insulating substrate; and an ion-selective electrode and a reference electrode disposed on the insulating substrate, 22. An ion sensor, wherein the reference electrode is the electrode according to claim 20 or 21.

28. 28. An apparatus for measuring components in a living body, comprising the ion sensor according to claim 26 or 27, which measures a sodium ion concentration contained in tissue fluid collected from a subject.

29. 28. A method for measuring a component in a living body, comprising measuring a sodium ion concentration contained in tissue fluid collected from a subject by the ion sensor according to claim 26 or 27.

Citation Information

Patent Citations

  • Ion sensor

    JP1992019554A

  • Electrochemical oxygen pump cell and nitrogen oxide detecting device using it

    JP2003329644A

  • Electrode, and solid oxide fuel cell and electrolytic device

    JP2015076210A

  • Solid electrolytic powder, electrode mixture material arranged by use thereof, and all-solid type sodium ion secondary battery

    JP2018018578A

  • Solid electrolyte body for gas sensor element, manufacturing method thereof and gas sensor element

    JP2018080963A